I need help with this proof for geometry.
Attachments:
![](https://hi-static.z-dn.net/files/d83/5808c0415f1ee3a64d9309eee8fbc6bd.jpg)
Answers
Answered by
1
Answer:
OK
Step-by-step explanation:
Answered by
1
Answer:
we have to prove it by SAS congruence
Step-by-step explanation:
WZ=ZS
angle wzd=angle wdz ( opposite angles of equal sides)
WD =SD
WZ=ZS
ZD =ZD (common)
therefore ∆WZD=∆ZSD (SAS)
Similar questions
Hindi,
3 months ago
Accountancy,
7 months ago
Math,
7 months ago
Math,
1 year ago
English,
1 year ago